Aggressive behavior in adolescent: The importance of biopsychosocial predictors among secondary school students - Fauzi, Fatimah Ahmad; Zulkefli, Nor Afiah Mohd; Baharom, Anisah (Frontiers in Public Health, 2023)
Overt aggression is a common type of aggression observed among adolescents, which is apparent and outward confrontational acts manifested physically and verbally, such as fighting and shouting. It has become a major public health concern, as it results in detrimental health impacts like injury, mental health, and social problems. An observational study was conducted among 16-year-old school students to determine their biopsychosocial predictors, using stratified proportionate population sampling. Pre-tested surveys were distributed to measure students’ aggression, biological, psychological, and social factors. A total of 463 students from four public secondary schools participated in the study, with a median aggression score was 23.00 (IQR=12.00). The significant predictors of aggression from multivariate analysis were Malay race, frequent dessert intakes, attitude towards aggression, low family income, and peer deviant affiliation (F [8, 244] =15.980, p<0.001, adjusted R2=0.290). Adolescent aggression determinants are collectively impacted as a result of biological, psychological, and social predictors and need to be focused on in interventional strategies.